Alabaster's Song - Lucado, Max; Nang Chan Yeema (Dallas, TX USA Word Publishing, 1996)
On Christmas Eve, a six-year-old boy listens to the angel from the top of the family tree sing just as he did on the first Christmas night.
Keywords: Christmas Books